Natural deep eutectic solvents as the major mobile phase components in high-performance liquid chromatography—searching for alternatives to organic solvents - Sutton, Adam T.; Fraige, Karina [UNESP]; Leme, Gabriel Mazzi [UNESP]; da Silva Bolzani, Vanderlan [UNESP]; Hilder, Emily F.; Cavalheiro, Alberto J. [UNESP]; Arrua, R. Dario; Funari, Cristiano Soleo [UNESP] (Springer Nature, 2018)
Over the past six decades, acetonitrile (ACN) has been the most employed organic modifier in reversed-phase high-performance liquid chromatography (RP-HPLC), followed by methanol (MeOH). However, from the growing environmental awareness that leads to the emergence of “green analytical chemistry,” new research has emerged that includes finding replacements to problematic ACN because of its low sustainability. Deep eutectic solvents (DES) can be produced from an almost infinite possible combinations of compounds, while being a “greener” alternative to organic solvents in HPLC, especially those prepared from natural compounds called natural DES (NADES). In this work, the use of three NADES as the main organic component in RP-HPLC, rather than simply an additive, was explored and compared to the common organic solvents ACN and MeOH but additionally to the greener ethanol for separating two different mixtures of compounds, one demonstrating the elution of compounds with increasing hydrophobicity and the other comparing molecules of different functionality and molar mass. To utilize NADES as an organic modifier and overcome their high viscosity monolithic columns, temperatures at 50 °C and 5% ethanol in the mobile phase were used. NADES are shown to give chromatographic performances in between those observed for ACN and MeOH when eluotropic strength, resolution, and peak capacity were taken into consideration, while being less environmentally impactful as shown by the HPLC-Environmental Assessment Tool (HPLC-EAT) metric. With the development of proper technologies, DES could open a new class of mobile phases increasing the possibilities of new separation selectivities while reducing the environmental impact of HPLC analyses.
Keywords: Green analytical chemistry; Green chromatography; Green solvents; Low transition temperature mixtures; NADES; Natural designer solvents